Analysis about the development of mobile electronic commerce: An application of production possibility frontier model - Shiro Uesugi; Hitoshi Okada (International Telecommunications Society (ITS), 2012)
This study aims to further develop our previous research on production possibility frontier model (PPFM). An application of model to provide analysis on the mobile commerce survey for which data was collected in Japan und Thailand is presented. PPFM looks into the consumer behaviors as the results form the perception on the relationship between Convenience and Privacy Concerns of certain electronic commerce services. From the data of consumer surveys, PPFM is expected to provide practical solution for service providers by offering useful information about what levels of trade-offs between Convenience and Privacy Concerns the service should be attained. This study provides a finding that the survey data seem to draw the oath of technology innovation PPFM.
Keywords: 330; Production Possibility Frontier; mobile commerce; electronic commerce